AzioInositols in the Treatment of Insulin-Mediated Diseases - Giovanna Muscogiuri; Stefano Palomba; Antonio Simone Laganà; Francesco Orio (International Journal of Endocrinology)
A growing body of research is currently focused on the role of inositol isomers and in particular myo-inositol (MYO-INS) and D-chiroinositol (DCI) in the treatment of insulin resistance states. Both isomers have been shown to exert insulin-mimetic action and to lower postprandial glucose. Further, insulin resistance-related diseases were associated to derangements in inositol metabolism. Thus, the aim of this review is to provide current evidence on the potential benefits of inositol isomers (MYO-INS and DCI) in the treatment of disease associated to insulin resistance such as polycystic ovary syndrome (PCOS), gestational diabetes, and metabolic syndrome. Finally, molecular insights into inositol insulin-sensitizing effects will be covered focusing on the possible role of inositol glycans as insulin second messengers.